Etika Politik Islam Dalam Pemikiran Nurcholis Majid - Suwandi, Ervina; Syamsul, Auliyah Shafira Azzahra; Naba, Khair Tasnim Razak; K, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses the contemporary Islamic thinker of the 20th century, namely Nurcholis Majid. The theoretical aim of this research is to provide an academic contribution to the concept of Islamic political ethics according to Nurcholis Majid. Practically, this research reveals the political ethics of a country according to Nurcholis Majid and the method of implementing Islamic political ethics according to Nurcholis Majid. Nurcholish Majid tries to dispel the myth of political Islam as dissent or opposition to the state by rejecting its symbolic and ideological character. Apart from that, this makes it clearer that Islam must emphasize its commitment to Islamic ethical values in every government system, especially in Nurcholis' view. implementation of Islamic ethical values. The research method used is a qualitative-interpretive method by conducting literature studies from secondary data in the form of books, journals and several documented research results. The data obtained will be collected, studied and synthesized and then analyzed carefully to get answers to the problems posed.